Training on Making Hand Sanitizers for Cadres During the Covid-19 Pandemic, Cibadak Village, Bogor City - Nuramalah, Fadhila; Masitha Arsyati, Asri (Universitas Ibn Khaldun, 2023)
Covid-19, which has become a global pandemic, has made many people take preventive measures. One way to prevent the transmission of Covid-19 is to maintain cleanliness such as diligently washing hands with soap using Hand Sanitizer. The purpose of this training is to provide knowledge to cadre mothers about how to make Hand Sanitizers during the Covid-19 pandemic. The partner in this service activity is RW.12 in Cibadak sub-district, Bogor City. Due to the limitations of Hand Sanitizer and to take advantage of time at home we can make our own Hand Sanitizer. This training activity was carried out for 1 time with three stages: 1) preparation, implementation, evaluation activities. This activity was carried out by Ibn Khaldun University Bogor Students who were accompanied by Field Supervisors, the results of this activity showed that the partners of this activity were able to make their own Hand Sanitizer.